Injection locked VCSEL based oscillator - ILVBO (2016)
Abstract Oscillators are present in all telecommunication systems. They synchronize the emitter and receiver of a message. The quality of the synchronization depends on the oscillator stability. To characterize the frequency domain oscillator stability, the phase noise of the carrier is used as figure of merit. An oscillator delivering a low phase noise carrier is a high spectral purity oscillator. Electronic oscillators are high performing at low frequencies. As communications systems require high data rate transmission, the electronic oscillators uses frequency multipliers that degrades the spectral purity of the carrier. The hybrid systems take advantage of the good performance of optical components at high frequency with the goal to be integrated in the electronic systems to overcome frequency limitation issues. This work use the optical injection locking technique by injecting the laser beam of a master laser inside the cavity of a VCSEL under direct modulation. The optical injection locking technique enlarges the direct modulation bandwidth of the VCSEL and reduces the Relative Intensity noise of the laser (RIN). The RIN reduction has as side effect the reduction of the additive noise inside the oscillator and, in consequence, reducing the oscillator phase noise.